Typology of Rainfed Rice Farmers' Social Actions in Ogan Ilir Regency, South Sumatra Province - Yulasteriyani, Yulasteriyani; Suwartapradja, Opan Suhendi; Mulyana, Nandang (Society, 2021)
Traditional farming communities are synonymous with subsistence culture, whereas modern society is a commercial economy. Economic action in sociology is called social action, which has different motives and orientations depending on the actor concerned. This research aims to analyze the socio-economic actions of farming communities in Kalampadu Village, Muara Kuang Sub-district, Ogan Ilir Regency, South Sumatra Province. This research uses a qualitative method. Informants in this research are rainfed rice farmers and stakeholders in Kalampadu Village and collect data using observation techniques, in-depth interviews, and documentation. The results showed that farmer actors in the village of Kalampadu carried out a dualism of economic action, both subsistence economics and commercial economics. Weber’s social action is not practiced partially. Some of these concepts of social action can be used simultaneously or separately. There are three models of social action in the socio-economic behavior of farmers, namely traditional social action (subsistence economy), traditional social action of rational instrumental integration (secondary subsistence economy), and rational social action (commercial economy).